Synthesis and characterization of 5-aryl-1,3,4-oxadiazole-2(3h)thione derivatives - Pathak, Shailesh; Sharma, Sharad; Pathak, Vinay; Prasad, Mahesh (Journal of Applied Pharmaceutical Research, 2020)
1,3,4-oxadiazoles represent a class of heterocyclic five membered compounds it contain two nitrogen and one oxygen of great importance in Pharmaceutical chemistry. This nucleus show four isomeric forms 1,2,4-oxadiazole,1,3,4-oxadiazole, 1,2,5-oxadiazole, and 1,2,3-oxadiazole. This nucleus has various biological activity such as antioxidant, antimicrobial, antifungal, antitumor, antidepressant, anticancer, analgesic etc.  have been reported. A series of 1,3,4-oxadiazoles-2(3H)thione derivative has been synthesized in four steps and the derivative were characterized by FTIR spectral analysis. This article explain the different biological activities associated with 1,3,4-oxadiazole five membered ring are useful for researchers across the world working on this nucleus.